Evaluation of Viral Inactivation on Dry Surface by High Peak Power Microwave (HPPM) Exposure. Issue 1 (14th February 2023) - Echchgadda, Ibtissam; Cantu, Jody C.; Butterworth, Joey; Gamboa, Bryan; Barnes, Ronald; Freeman, David A.; Ruhr, Francis A.; Williams, Weston C.; Johnson, Leland R.; Payne, Jason; Thomas, Robert J.; Roach, William P.; et al.
Abstract : Previous research has shown that virus infectivity can be dramatically reduced by radio frequency exposure in the gigahertz (GHz) frequency range. Given the worldwide SARS‐CoV‐2 pandemic, which has caused over 1 million deaths and has had a profound global economic impact, there is a need for a noninvasive technology that can reduce the transmission of virus among humans. RF is a potential wide area‐of‐effect viral decontamination technology that could be used in hospital rooms where patients are expelling virus, in grocery and convenience stores where local populations mix, and in first responder settings where rapid medical response spans many potentially infected locations within hours. In this study, we used bovine coronavirus (BCoV) as a surrogate of SARS‐CoV‐2 and exposed it to high peak power microwave (HPPM) pulses at four narrowband frequencies: 2.8, 5.6, 8.5, and 9.3 GHz. Exposures consisted of 2 µs pulses delivered at 500 Hz, with pulse counts varied by decades between 1 and 10, 000. The peak field intensities (i.e. the instantaneous power density of each pulse) ranged between 0.6 and 6.5 MW/m 2, depending on the microwave frequency. The HPPM exposures were delivered to plastic coverslips containing BCoV dried on the surface. Hemagglutination (HA) and cytopathic effect analyses were performed 6 days after inoculation of host cells to assess viral infectivity. No change in viral infectivity was seen with increasing dose (pulse number) across the tested frequencies. Under all conditions tested, exposure did not reduce infectivity more than 1.0 log10. For the conditions studied, high peak power pulsed RF exposures in the 2–10 GHz range appear ineffective as a virucidal approach for hard surface decontamination. © 2023 Bioelectromagnetics Society.